IMPLEMENTATION OF TEACHING MATERIALS USING A REALISTIC MATHEMATICS EDUCATION APPROACH IN PRIMARY STUDENT MATHEMATICS COMMUNICATION - Rabbani, Sylvia; Muftianti, Agni (PrimaryEdu : Journal of Primary Education, 2020)
The main problem in this study is the lack of student communication skills and the lack of RME-based teaching materials that use used goods as a learning medium. The long-term objective of the research to be carried out is to support quality improvement and development of basic and regional education policies at the local and national levels through improving the quality of Indonesia's young generation of hope. The purpose of this study was to obtain an overview of the results of the implementation of teaching materials "mathematics learning in elementary schools". The focus of this research problem is: 1) learning steps using teaching materials and 2). Barriers are felt when learning using these teaching materials. And 3). The implementation of teaching materials uses a realistic mathematics education approach in the communication skills of PGSD students with the help of teaching aids made from used materials. The method used is descriptive qualitative, this study describes the application of elementary mathematics learning teaching materials in mathematics communication of students at the PGSD Siliwangi Teacher Training College and the obstacles in implementing teaching materials. The results of this study were the steps for implementing elementary mathematics teaching materials in mathematics communication for PGSD students..